Mentoring with(in) care: A co‐constructed auto‐ethnography of mutual learning. (23rd April 2015) - Snoeren, Miranda M. W. C.; Raaijmakers, Ragna; Niessen, Theo J. H.; Abma, Tineke A.
Summary: Research into workplace mentoring is principally focussed on predictors and psychosocial and instrumental outcomes, while there is scarcely any in‐depth research into relational characteristics, outcomes and processes. This article aims to illustrate these relational aspects. It reports a co‐constructed auto‐ethnography of a dyadic mentoring relationship as experienced by mentor and protégé. The co‐constructed narrative illustrates that attentiveness towards each other and a caring attitude, alongside learning‐focussed values, promote a high‐quality mentoring relationship. This relationship is characterised, among other things, by person centredness, care, trust and mutual influence, thereby offering a situation in which mutual learning and growth can occur. Learning develops through and in relation and is enhanced when both planned and unplanned learning takes place. In addition, the narrative makes clear that learning and growth of both those involved are intertwined and interdependent and that mutual learning and growth enrich and strengthen the relationship. It is concluded that the narrative illustrates a number of complex relational processes that are difficult to elucidate in quantitative studies and theoretical constructs. It offers deeper insight into the initiation and improvement of high‐quality mentoring relationships and emphasises the importance of further research into relational processes in mentoring relationships. Copyright © 2015 John Wiley & Sons, Ltd.